High-resolution stable isotope stratigraphy of the upper Cambrian and Ordovician in the Argentine Precordillera: Carbon isotope excursions and correlations - Sial, A. N. (2012)
We report the occurrence of important carbon isotope excursions in early Paleozoic formations of the Eastern and Central Argentine Precordillera. The Steptoean positive isotope carbon excursion (SPICE) is known from North America, Kazakhstan, South China, Australia and South America, and the negative isotope carbon excursion (SNICE) has been described for the first time in South America. We report here the record of the SPICE and SNICE in a single section in the Eastern Precordillera. In the Central Precordillera, a minor middle Darriwilian positive carbon isotope excursion (MDICE) and a late Sandbian positive isotope carbon excursion, the GICE (~ + 3‰; C. bicornis biozone) are reported from two sections. One pre-GICE positive carbon-isotope excursion (Sandbian Sa1, N. gracilis biozone) in the Central Precordillera with a δ13C peak of ~ + 2‰ is, perhaps, equivalent to the positive Spechts Ferry δ13C excursion of North America. A positive δ13C excursion (~ 6‰; N. persculptus biozone) recorded at the base of the late Hirnantian La Chilca Formation probably corresponds to HICE. These carbon-isotope excursions resulted from more than one factor where paleoceanographic events probably played a major role: (a) sea-level fall and vigorous fluctuations in the Steptoean (SPICE), (b) sea-level rise in the Sunwaptan (SNICE), (c) important transgression in the Sandbian (pre-GICE and GICE), and (d) sea-level fall in the late Hirnantian (HICE). In the Darriwilian and Sandbian stages, organic burial has led to a large 12C sequestration in the deep anoxic ocean with saline bottom water, recorded by the graptoliferous black shales of the Gualcamayo and Los Azules formations in Central Precordillera, helped the building of the MDICE and GICE anomalies. δ18O values for the Upper Cambrian carbonates are likely near-primary isotope signals that point to progressive cooling from the SPICE to the SNICE, whereas for Sandbian carbonates they suggest strong temperature fluctuations. The δ13C peak of the GICE coincides with a cooler period with temperatures warming up towards the late Hirnantian to Rhuddanian. The Upper Cambrian to the Middle Ordovician of the Precordillera recorded a decrease of seawater 87Sr/86Sr ratios in accordance to the global picture. This decrease probably reflects the influence of widespread volcanic activity from arc terranes in low-latitude settings along eastern margins of Laurentia and in the Argentine Precordillera in the Early to Middle Ordovician. Five carbonate samples (from San Juan, Gualcamayo and Los Azules formations) yielded εNd values that along seven already published values seem to plot along the Nd isotopic evolution trend of the Iapetus Ocean. Together, the record of global Upper Cambrian and Ordovician carbon-isotope excursions in the Argentine Precordillera is a valuable proxy in refining Early Paleozoic stratigraphy, establishing of regional/global high-resolution correlations, and sea-level change history in South America.